Pengaruh Proses Menulis dan Kognitif terhadap Kemampuan Menulis Teks Naratif Siswa - Lati Andriani; Syihabuddin Syihabuddin; Andoyo Sastromiharjo; Dadang Anshori (Universitas Mulawarman, 2023)
This study aimed to investigate the aspects of an individual's writing process that play an important role in improving the quality of writing products, as well as the role of individual cognition on the quality of writing products. A factorial analysis design was used in this study. The results of this study, first, the aspects of spontaneous revision and vocabulary revision affect the quality of writing. In addition, it was also found that students with better reading ability tended to do more intensive online revision. Second, the process aspects that affect the quality of students' narrative writing are spelling ability and the number of revisions. In addition, students' cognitive abilities also have a significant influence on their writing ability. The aspects of cognitive ability that influence are oral language ability, reading, vocabulary selection, capitalization, and spelling. The process aspects that play an important role in improving narrative writing skills are spelling and reading cognitive abilities. The processes that contributed significantly to improving writing quality were oral language ability, attention, and working memory.